Surface decontamination of fresh-cut pennywort (Centella asiatica L.) leaves through pulsed light technology and acidic electrolysed water - Rosli, Siti Zaharah (2022)
Minimally processed vegetables are in high demand as it is convenient and have freshlike quality. However, it remains the main cause of foodborne outbreaks. These outbreaks are allied with the consumption of fresh-cut products such as pennywort (Centella asiatica) leaves. Pennywort is an herbaceous vegetable that is usually eaten fresh as ‘ulam’ or salad. Fresh-cut products are exposed to faster many physiological changes that lead to the biochemical and microbiological deterioration that affect the quality and shelf-life. Thus, this research aimed to extend the shelf life of fresh-cut pennywort by the potential applications of pulsed light (PL) treatment and acidic electrolysed water (AEW) in reducing microbial load, retain physicochemical qualities, physiological changes, nutritional values and acceptance of sensory quality during refrigerated storage. The reduction of inoculated Escherichia coli on the pennywort leaves after exposure to PL was examined and viewed using the scanning electron microscopy. The effect of sample weight and leaves arrangement using PL fluence on the microbiological properties of fresh-cut pennywort leaves were evaluated. PL at a fluence of 6.9 J/cm2 was found to be the optimal fluence for reducing total plate counts while keeping the physical qualities of pennywort leaves and increasing shelf life to approximately 12 days, while control sample about 8 days. Unfortunately, higher PL fluence (9.6 and 12.3 J/cm2) exposure negatively affected the visual quality of the leaves. The inactivation of E. coli population was significantly higher at PL fluence of 6.9 J/cm² with the value of reduction about 2.27 log CFU/g. Sample weight, sample arrangement and pre-treatment step were able to reduce microbial loads in pennywort leaves and were found necessary to maximise impact of pulsed light. Exposure to PL was effective when smaller sample weight was used, where 5 g > 10 g > 15 g with the significant highest log reduction were 0.64 log CFU/g and 0.55 log CFU/g for TPC and YM, respectively for 5 g. In term of sanitiser efficacy, acidic electrolysed water (AEW) was shown to be the most effective in preserving the physiological and physicochemical properties of pennywort and was highly accepted by consumers based on sensory quality. The combination of PL treatment and AEW indicated a synergistic effect. Higher microbial reduction was achieved about 1.80 and 1.11 log CFU/g (TPC and YM) of fresh-cut pennywort leaves through combination of PL technology and AEW and preserved the fresh-like sensory quality of pennywort leaves. Meanwhile, the bioactive compounds from triterpene glycosides namely, asiaticoside, madecassoside, asiatic acid, and madecassic acid are preserved. In conclusion, the combination of pulsed light technology and acidic electrolysed water was effective to extend shelf life of fresh-cut pennywort leaves up to 16 days by ensuring its safety while maintaining the physicochemical, nutritional and sensory qualities during storage at 4±1 °C.